An Experimental Study of the Rheological Properties and Stability Characteristics of Biochar-Algae-Water Slurry Fuels. (May 2017) - Liu, Pengfei; Zhu, Mingming; Leong, Yee-kwong; Zhang, Yang; Zhang, Zhezi; Zhang, Dongke
Abstract: The rheological properties and stability characteristics of biochar-algae-water slurry fuels were experimentally investigated. Algae Chlorella vulgaris in dry powder form was mixed with a pine sawdust biochar with algae content varying from 0 to 100wt%. Biochar-algae-water slurry fuels were then prepared by dispersing the mixtures in deionised water. Lignosulfonic acid sodium salt (LASS) was added as a dispersant at 2wt% on the basis of weight of the solid. The apparent viscosity and shear stress were measured at varied shear rate using a Haake VT550 cone and plate viscometer. The stability of the slurry fuels was characterised using a "drop rod" method. For a given solid loading, as algae content increased, the slurry fuel displayed higher viscosity and more apparent shear-thinning behaviour due to the enhanced flocculation of solid particles. The slurry stability was also improved as the algae content increased.